Simulation of the properties of a frying composition based on ostrich oil and СО2-marjoram extract - M. V. Gorbacheva; V. E. Tarasov; I. M. Chebanov (Новые технологии)
The article reveals the optimization of a fat frying composition formulation based on ostrich oil and natural stabilizing additive using mathematical modeling of its component composition and analysis of the qualitative characteristics of the product. The object of the research was experimental versions of the frying composition obtained according to the developed recipes, which included liquid and solid fraction of ostrich oil in the following ratio, wt. %: 30,0–70,0 – the liquid one, 30,0–70,0 the solid one and 0,01–0,20 CO2 -marjoram extract. The selection and ratio of the components of the frying fat recipe was carried out using the mathematical modeling methods based on the Scheffe-simplex lattice design. A comparative analysis of the consumer properties of the fat frying composition was carried out using E.K. Harrington’s desirability function. It was shown that the best technological and qualitative characteristics of the properties of the fat frying composition were established at a ratio of 0,5 percent of liquid or 0,5 solid fractions of the frying composition mass with the addition of at least 0,1 wt. % CO2 -extract of marjoram. Positive results were also noted in samples with a minimum solid fat content of 30,0 wt. %, but with a significant amount of a stabilizing additive – 0,15 wt. %. The inhibiting effect of the introduced natural additive, which slowed down oxidative processes in the process of frying the product, were proven. It was determined that only experimental versions of deep-frying fat in the established optimum of the quantitative ratio of fractions and CO2 - extract had the highest desirability scores of 0,723 and 0,792, confirming the high level of product quality. In addition, the proposed combination of ingredients provided an increase in the time of use of the deep-frying composition, due to the increased resistance to oxidation.